Elaboración de un plan de emergencia mediante la identificación y análisis de los factores de riesgo en la empresa Centro Agrícola de Salcedo - Guagchinga Moreno, Bryan Israel (2022)
This research project was carried out at the Centro Agrícola de Salcedo, in which an emergency plan has been prepared by carrying out an analysis of the infrastructure, the different risks that can affect the areas of the company in the event of a emergency. In order that, in the event of an eventuality, action can be taken and immediate measures can be taken to protect the well-being of people. Through the identification and analysis of risks, using the GTC45 Matrix, we proceeded to detail the vulnerabilities, threats, dangers to develop strategies, protection elements, detectors in the presence of a fire. In the event of a natural phenomenon, due to the location of the facilities, evacuation routes, safe points, emergency brigades were detailed, with the use of regulations, which become a development guide for decision-making.